The Gotong Royong Run: An Educational Game to Build the Spirit of Togetherness among Players - Mulyadi Guntur Waseso (Universitas Negeri Malang, 2016)
The spirit of togetherness and cooperation seems to be declining among some of Indonesian communities. The Independence Day celebration can be used as a momentum to strengthen the spirit through various competitions for children. Traditional games which are commonly played for competitions can potentially be developed into educational games. The Gotong Royong Run presented here has been developed and modified from a traditional game called Lari Me-mindahkan Bendera (Flag-moving Race). The game is intended for pre-school and elementary school children to train skills of working cooperatively